Image-Guided Percutaneous Biopsy and Drainage of the Abdomen - Arellano, Ronald S. (Digestive Disease Interventions, 2018)
Image-guided percutaneous biopsy and abscess drainages are some of the most commonly performed procedures in interventional radiology. With advances in targeted immunotherapies for oncology patients, physicians increasingly depend on the experience and skill of the interventional radiologist to acquire tissue specimens from within the abdomen and pelvis. Furthermore, percutaneous drainage of abdominal and pelvic fluid collections has largely replaced the need for surgical interventions for infected abdominal collections. This review will discuss techniques of image-guided percutaneous abdominal biopsy and drainage.
Keywords: fine needle aspiration; core biopsy; liver; pancreas; spleen